2008
DOI: 10.1590/s1413-70542008000300041
|View full text |Cite
|
Sign up to set email alerts
|

Controle genético da incompatibilidade do cruzamento entre cultivares andinas e mesoamericanas de feijoeiro comum

Abstract: RESUMONormalmente, ocorre incompatibilidade nos cruzamentos entre feijoeiros de origem andina com mesoamericanas. Há dúvidas no controle genético do caráter. Singh & Gutiérrez (1984) relataram que no controle do caráter estão envolvidos dois genes e ocorre epistasia recessiva dupla. Vilarinho (2004) apresentou resultados, relatando que não seriam apenas dois genes. Para melhor elucidar o controle genético desse caráter foi realizado o presente trabalho. Para isso, a cultivar de origem andina Jalo EEP 558 foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…Grande parte das fontes de genes quanto à precocidade estão em feijões de origem andina (Welsh et al, 1995), e grãos com padrão comercial, de modo geral, são de origem mesoamericana. Em alguns cruzamentos entre os dois conjuntos gênicos, observa-se incompatibilidade, o que inviabiliza ou causa diversas anormalidades nas plantas F 1 , tais como nanismo, folhas cloróticas, esterilidade, crescimento radical reduzido e formação de raízes adventícias no hipocótilo (Arantes et al, 2008).…”
Section: Introductionunclassified
“…Grande parte das fontes de genes quanto à precocidade estão em feijões de origem andina (Welsh et al, 1995), e grãos com padrão comercial, de modo geral, são de origem mesoamericana. Em alguns cruzamentos entre os dois conjuntos gênicos, observa-se incompatibilidade, o que inviabiliza ou causa diversas anormalidades nas plantas F 1 , tais como nanismo, folhas cloróticas, esterilidade, crescimento radical reduzido e formação de raízes adventícias no hipocótilo (Arantes et al, 2008).…”
Section: Introductionunclassified
“…According to Ougham et al (1996), the N 1 allele has an effect on lignin deposition The presence of hulled grains in homozygous genotypes (N 1 N 1 N 2 N 2 ) may also be associated with incomplete penetrance and/or variable expressiveness of the genes; i.e., the genotype has the gene which exhibits the naked characteristic; nevertheless, the frequency of expression of the phenotype is less than 100%, as was observed in the naked parental genotype and in other studies of this trait in oats (Valentine 1995, Cabral et al 2000. In this sense, alteration in the expected segregations may be attributed to differences in the penetrance and expressiveness of the genes as a result of the environmental effect (Arantes et al 2008).…”
Section: Resultsmentioning
confidence: 85%
“…However, the generation of higher genetic diversity by crossing Andean and Mesoamerican cultivars in several situations is not possible due to the occurrence of genetic incompatibility in the F 1 plants (Vieira et al, 2005). This incompatibility is manifested by dwarfism or weakness in the F 1 hybrid, whose plants die or have poor growth, and exhibit a number of changes including sterility, reduced root growth, chlorotic leaves, absence of roots, and the formation of adventitious roots on the hypocotyl region (Vilarinho et al, 2004;Vieira et al, 2005;Arantes et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the F1 generation, the genotype would be DL 1 dl 1 DL 2 dl 2 , and the presence of dominant alleles of the two genes would lead to incompatibility. However, Arantes et al (2008) observed that the 'incompatibility' trait has a very variable expression, and there is variation in the plant development stage in which the symptoms manifest.…”
Section: Discussionmentioning
confidence: 99%